Community structure of phytoplankton in seagrass beds in the waters of Balikpapan City Bay, East Kalimantan - Shavira Malianda Sari; Jailani Jailani; Nurfadilah Nurfadilah (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Seagrasses are flowering plants that live in shallow waters and form an ecological community which is a place for biotic and abiotic interactions. The structure of the phytoplankton community consists of individual arrangements of various types and species that are organized to form a community. Phytoplankton are autotrophic organisms and primary producers in the marine food chain. The purpose of this study was to determine the abundance of phytoplankton, uniformity and dominance values. Measurement of water quality parameters was carried out at the Water Quality Laboratory, Faculty of Fisheries and Marine Sciences, Mulawarman University from November to December. Determination of research locations using the method of consideration (purposive sampling method). Sedgewick-Rafter method was applied for the identification stage. The data were analyzed by calculating the abundance of phytoplankton, diversity index, uniformity index and dominance index, then the data were analyzed using Microsoft Excel. The abundance of phytoplankton ranged from 2772 - 1575 individuals/L. While the diversity index values ​​ranged from 2.79 - 2.57, the uniformity index values ​​ranged from 0.74 - 0.80 and the dominance index values ​​ranged from 0.10 - 0.11.